2023
DOI: 10.1186/s12889-023-15022-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to cervical cancer screening recommendations among women in Eswatini: a cross-sectional study

Abstract: Background In 2018, Eswatini had the world's highest age-standardised cervical cancer incidence rate. Cervical cancer screening reduces women’s risk of invasive cervical cancer. Data on adherence to cervical cancer screening recommendations in Eswatini are scarce. The purpose of the current study was to determine Eswatini women’s self-reported adherence to cervical cancer screening recommendations, attitudes toward screening, and factors associated with non-adherence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…The current study is a sub-study of a larger one reported elsewhere [ 36 ], which investigated non-adherence to cervical cancer screening recommendations among women in Eswatini. The aims of this larger study informed the sample size of 377 for the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The current study is a sub-study of a larger one reported elsewhere [ 36 ], which investigated non-adherence to cervical cancer screening recommendations among women in Eswatini. The aims of this larger study informed the sample size of 377 for the current study.…”
Section: Methodsmentioning
confidence: 99%